UNDERSTANDING THE CONCEPT OF SPUR DIMENSIONS REVIEWED BY THE TERMS OF GENDER DIFFERENCES AND ABILITY CATEGORIZED BY STUDENTS AT MADRASAH IBTIDAIYAH - Hajra Yansa; Murniati Muniati; Nurrahmah Nurrahmah; Nurhayati Nurhayati; Ani Fitriyani (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
These gender differences and abilities categorized by students at Madrasah Ibtidaiyah (Islamic Elementary School in the Ministry of Religious Affairs, Indonesia) can understand the concept of SPUR dimension fractions (Skills, Property, Uses, and Representation) that is the focus of this study. Presently, it is to answer the study's neediness about gender differences in math performance recommended by the previous studies. To offer the novelty about the measurement of conceptual understanding in four dimensions because one dimension is not relevant to describe students' understanding comprehensively and deeply of mathematical concepts. This study was a qualitative descriptive that relies on the analysis of test participants' answers; it consists of three male students and three female students representing the high, medium, and low ability categories at Madrasah Ibtidaiyah of Indramayu Regency. The students' participant is determined by purposive sampling. The analysis of the test participants' answers demonstrated the ability to understand the concept of fractions in the SPUR dimension of equality between male and female students in the same ability category. However, the students at every level of ability to achieve a different dimension. Male and female students in the high category achieved the dimensions of skills and property. Male and female students in the medium and low categories achieved skills. High-ability students and the medium category experienced an integer bias error using the integer property infractions. They perform arithmetic operations in the numerator and denominator separately as if they were independent integers. For this reason, students need to develop an understanding of concepts, especially on the dimensions of fraction properties, applications, and their representations, without being influenced by gender stereotypes. This development of understanding can be done through SPUR dimensional exercises that avoid gender bias, and teachers establish communication mathematics teaching in the classroom to engage students in both men and women.